Biocompatible heterogeneous bone incorporated with polymeric biocomposites for human bone repair by 3D printing technology. Issue 13 (24th November 2020) - Wan, Meiling; Liu, Shuifeng; Huang, Da; Qu, Yang; Hu, Yang; Su, Qisheng; Zheng, Wenxu; Dong, Xianming; Zhang, Hongwu; Wei, Yen; Zhou, Wuyi
Abstract: Polylactic acid (PLA) has become a popular polymer material due to its superior biocompatibility. At present, there are a few relevant research on heterogeneous bone powder. Besides, the poor dispersibility and adhesivity of inorganic particles in the organic phase remains a problem. In this study, the pork bone powders were modified with N‐butanol to improve its dispersibility and compatibility in the PLA matrix. In addition, polybutylene succinate‐co‐terephthalates (PBSA) was applied as a flexibilizer to further reinforce the mechanical properties of materials. The composite filaments with a diameter of 1.75 ± 0.05 mm containing 10 wt% of modified bone powder, 10 wt% PBSA and 80 wt% PLA were prepared by a melt blending method. The obtained results showed that modified particles were uniformly dispersed within the PLA matrix and improved the mechanical properties of the composite filaments with a tensile strength of 48.5 ± 0.2 MPa and a bending strength of 79.1 ± 0.1 MPa and a notch impact strength of 15.8 ± 0.3 kJ/m 2 . And the prepared composite materials contained low cytotoxicity, high biocompatibility and printability, which verified the feasibility of it in 3D printing personalized bone repair applications. This provides a theoretical basis for further research on the effect of bone repair in vivo. Therefore, the composite material will have potential applications such as making customized bones and bone scaffolds by three dimensional printing technology. Abstract :